Strategi Personal Branding Habib Ja'far dalam Kegiatan Dakwah di Youtube (Analisis Deskriptif pada Akun Youtube "Jeda Nulis") - Fadhlurrahman, Faiz Imam; Ridwan, Aang; Astuti, Dyah Rahmi (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to explain Habib Ja'far's personal branding strategy in da'wah activities on Youtube. This study uses descriptive analysis method, using passive participatory observation techniques, in-depth interviews and documentation studies. This research uses authentic personal branding theory from Hubert K. Rampersad. The results of the study show that Habib Ja'far's personal branding on Youtube includes authentic personal branding theory, including: 1) Authentiity, 2) Integrity, 3) Consistency, 4) Specialization, 5) Authority, 6) Distinctivness, 7) Relevant, 8) Visibility, 9) Persistence, 10) Goodwill, 11) Performance of Habib Ja'far's personal branding strategy on Youtube social media.